2022
DOI: 10.1155/2022/6767428
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Uniaxial Compression Mechanical Properties of Rubber Powder Recycled Coarse Aggregate Concrete Based on Strain Energy Theory

Abstract: In order to develop and make full use of waste construction concrete and waste tyre rubber powder, the experiment entirely used recycled coarse aggregate to replace natural crushed stone aggregate and investigated the effect of different mesh sizes of rubber powder (20 mesh, 60 mesh, and 100 mesh) on the uniaxial compressive mechanical properties, strain energy density, and pore structure of recycled coarse aggregate concrete at three curing ages (14 d, 28 d, and 90 d). Based on the strain energy theory, fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…CRC is a composite based on ordinary concrete that is formed by adding finer crumb rubber to replace some of the fine aggregate or larger crumb rubber to replace some of the coarse aggregate. Research has shown that CRC outperforms ordinary concrete in terms of energy absorption and consumption [ 13 , 14 ], fatigue resistance [ 15 ], reducing material brittle failure [ 16 ], deformation capacity [ 17 ], hindering crack development [ 18 ], durability [ 19 , 20 , 21 ], and thermal performance [ 22 ]. To reduce the degree of brittle failure of deep foundation pit support structures, the application of CRC to deep foundation pit support has been studied [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…CRC is a composite based on ordinary concrete that is formed by adding finer crumb rubber to replace some of the fine aggregate or larger crumb rubber to replace some of the coarse aggregate. Research has shown that CRC outperforms ordinary concrete in terms of energy absorption and consumption [ 13 , 14 ], fatigue resistance [ 15 ], reducing material brittle failure [ 16 ], deformation capacity [ 17 ], hindering crack development [ 18 ], durability [ 19 , 20 , 21 ], and thermal performance [ 22 ]. To reduce the degree of brittle failure of deep foundation pit support structures, the application of CRC to deep foundation pit support has been studied [ 16 ].…”
Section: Introductionmentioning
confidence: 99%